Modern options in coloproctology: transanal endoscopic surgery - O. I. Kit; Yu. A. Gevorkyan; N. V. Soldatkina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To estimate results of transanal endoscopic resection of rectal tumors and to analyze literature data devoted to this method.Key points. Experience of Rostov Scientific Research Institute of Oncology has allowed to confirm literature data and to turn out perspective approaches to application of transanal endoscopic resection of tumors. It was found, that transanal endoscopic resection of benign tumors and early stages of malignant tumors of rectum is a modern, highly effective method of treatment that provides radical tumor removal within any layer of rectal wall and adjacent mesorectal soft tissue due to application of exact tools and precision technic of the intervention, it preserves intestinal function as well.Conclusion. Described options allow recommending this method to broad application in surgical practice. According to received results it is possible to conclude, that transanal endoscopic tumor resection can become a method of choice at initial stages of rectal cancer.